Assessing Dietary Quality of Older Chinese People Using the Chinese Diet Balance Index (DBI) - Xu, Xiaoyue (PLoS One, 2015)
BACKGROUND/OBJECTIVES: Few studies have applied the Chinese Diet Balance Index (DBI) in evaluating dietary quality for Chinese people. The present cross-sectional study assessed dietary quality based on DBI for older people, and the associated factors, in four socioeconomically distinct regions in China. METHODS: The China Health and Nutrition Survey (CHNS) involves 2745 older Chinese people, aged 60 or over, from four regions (Northeast, East Coast, Central and West) in 2009. Dietary data were obtained by interviews using 24 hour-recall over three consecutive days. Four indicators: Total Score (TS), Lower Bound Score (LBS), Higher Bound Score (HBS) and Diet Quality Distance (DQD) from DBI were calculated for assessing dietary quality in different aspects. RESULTS: 68.9% of older people had different levels of excessive cereals intake. More than 50% of older people had moderate or severe surplus of oil (64.9%) and salt (58.6%). Intake of vegetables and fruit, milk and soybeans, water, and dietary variety were insufficient, especially for milk and soybeans. 80.8% of people had moderate or severe unbalanced diet consumption. The largest differences of DQD scores have been found for people with different education levels and urbanicity levels. People with higher education levels have lower DQD scores (p<0.001), and people living in medium and low urbanicity areas had 2.8 and 8.9 higher DQD scores than their high urbanicity counterparts (p<0.001). Also, significant differences of DQD scores have been found according to gender, marital status, work status and regions (p<0.001). CONCLUSION: DBI can reveal problems of dietary quality for older Chinese people. Rectifying unbalanced diet intake may lead to prevention of non-communicable diseases (NCDs). Dieticians and health care professionals need to increase dissemination and uptake of nutrition education, with interventions targeted at regions of lower socioeconomic status.